Comparison of Washing and Swabbing Procedures for Collecting Genital Fluids To Assess Cervicovaginal Shedding of Herpes Simplex Virus Type 2 DNA - Ndjoyi-Mbiguino, Angélique (American Society for Microbiology, 2003)
Asymptomatic genital shedding of herpes simplex virus type 2 (HSV-2) DNA was evidenced by real-time PCR in 25 (13.2%) of 188 cervicovaginal lavage samples and in only 13 (6.9%) paired cervicovaginal samples from 188 HSV-2-seropositive, nonpregnant childbearing-aged human immunodeficiency virus-seronegative women living in Gabon. These observations demonstrate that cervicovaginal washing is more suitable than endocervicovaginal swabbing for detecting and quantifying HSV-2 DNA by PCR in female genital secretions.